Transporting highly concentrated slurries with centrifugal pumps : the thickened minerals tailings example - Wennberg, Thord (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2010)
New technologies are continuously considered for the handling and deposition of tailings. With thickened tailings only a fraction of water used conventionally reaches the disposal area, thus limiting sizes of water holding dam facilities and areas to be rehabilitated. Heat may also be recovered with direct water circulation from the thickening. Technical-economical feasibility considerations are here coupled to the Svappavaara iron ore operations by the Luossavaara-Kiirunavaara AB (LKAB) Company in northern Sweden. Local conditions here favour placement with an elevated thickener location close to the disposal area.The thickened tailings studied here have typically average particle sizes of 20 to 100 µm with maximum sizes of up to about 500 µm. The corresponding slurries cover an intermediate area between homogeneously and heterogeneously flowing mixtures. Various design features are often refereed to in rheological terms, i.e. homogeneous flow. Here, these terms are considered with some caution due to the notable amount of particles larger than about 40 µm.The objective is to form a background for feasibility considerations based on laboratory and pilot-scale experiments in pipelines and flumes together with viscometric measurements and depositional slope observations. Pipeline diameters covered the full-scale range, up to 0.15 m.It was found that a solids concentration by volume of about 48 % characterizes the pipeline pumping, here estimated to be on the conservative side with respect to thickened product quality requirement. The overall pipeline loop results were evaluated in terms of a representative pipe wall stress of about 200 Pa. Approximate values of the Bingham yield stress and plastic viscosity were estimated to 185 Pa and 0.03 Pas, respectively. Depositional slopes have been estimated to about 4 % for slurry properties that gives a conceptually even inclination with no segregation of particles and virtually no drainage of water.With an elevated thickener location close to the disposal area a new ...